The role of CpNifS in selenium and sulfur plant metabolism: implications for phytoremediation and photosynthesis - Van Hoewyk, Doug, author; Pilon, Marinus, advisor; Pilon-Smits, Elizabeth, advisor (Colorado State University. Libraries, 2008)
NifS-like proteins are a conserved group of proteins that can cleave the sulfur-containing amino acid cysteine in alanine and elemental sulfur (S), and selenocysteine alanine and selenium (Se). In yeast and bacteria, NifS-like proteins are essential for survival because they provide the S for iron(Fe)-S clusters, a prosthetic group that is inserted into various FeS proteins that have a role in electron transfer. Furthermore, NifS-proteins are an essential part of Se metabolism in organisms that require this trace element. The goal of this research was to characterize the function of a chloroplastic NifS-like protein in Arabidopsis thaliana, designated AtCpNifS. As described in this dissertation, overexpression of CpNifS increases plant tolerance to selenate and accumulation of Se. Increased levels of CpNifS prevents toxic incorporation of selenocysteine into proteins, and thus enhances Se tolerance. This may benefit phytoremediation-the use of plants to naturally clean polluted soils and groundwater. In an effort to further the field of phytoremediation, a transcriptome experiment was performed in order to identify other genes and pathways that are involved in responding to Se stress. However, as divulged, plants likely do not require Se for essential metabolism, and the true function of CpNifS is more likely in the maturation of FeS clusters. The knockdown of CpNifS proteins in Arabidopsis using an inducible RNAi approach revealed that chloroplast function and structure became impaired, and that levels of all tested FeS proteins decreased. Consequently, the rate of photosynthetic electron transport, which is dependent on FeS proteins, diminished, and plants became chlorotic and eventually died. Therefore, CpNifS is required for FeS proteins, and is essential for proper photosynthesis and plant growth.
Keywords: CpNifS; photosynthesis; phytoremediation; selenium; sulfur; ecology; plant sciences